The effect of the ethanol extract of Typhonium flagelliforme on apoptosis adenocarcinoma mamma cells in C3H mice - Chodidjah, -; Dharmana, Edi; Susanto, Hardhono; Ekawuyung, Puspita (Bangladesh Journal of Medical Science, 2023)
Malignancy cause high impact in mortality in worldwide. Typhonium Flagelliforme have been known to improve the immune system. The aims of this study was to determine the effects of Typhonium Flagelliforme on the tumor necrosis factor alpha (TNF-α) level and percentage of apoptotic cells in mice tumor The post test study design with randomized control group of 24 C3H mice with tumor were divided into 4 groups: I (control), 2 ; 3; and 4 (treatment). All treatment were given 0.2 cc of extract at the dose of 200, 400 and 800 mg/kgBW respectively for 30 days. TNF-α level was from tumor tissue were measured using ELISA methods, and percentage of apoptotic cells from tumor tissue were determined using immunohistochemistry assay with TUNEL antibody. The mean difference of TNF-α expression was tested using Anova at the significant level of 0.05. Apoptotic cells was analyzed by Mann Whitney. The result indicate that average of TNF α level in the treated groups were higher than those of control group (p<0.05). The percentage of apoptotic cells at the dose 200 mg/KgBW was higher than that of control group, groups 2 and 3(P<0.05). In conclusion, Typhonium Flagelliforme can increase in the percentage of apoptosis cells but not in the levels of TNF α Bangladesh Journal of Medical Science Vol. 22 No. 02 April’23 Page : 329-335